The Effects of Variation In Muscular Strength and Flexibility Training On the Development of Motor Response Speed In Goalkeepers Of The Ages 15 – 16 years old - GALIL, Qahtan (Journal of Physical Education, 2009)
Programmed and organized training based on modern scientific knowledge has an essential role in reaching the highest levels and results. The importance of the study lies in the effect of using variation in muscular strength and flexibility training on the development of motor response speed in goalkeepers of the ages 15 – 16 years old. The problem of the study lies in the coaches' weakness and negligence in training muscular strength and flexibility. They usually relay on ineffective traditional exercises that led researcher to come up with such studies as this. The study aimed at designing two various training programs each for certain training; the first for training muscular strength while the second aimed at training flexibility. The researcher also aimed at identifying the effect of these training programs on the speed of motor response speed in football goalkeepers. The researcher hypothesized that muscular strength training positively affect the speed of motor response speed in football goalkeepers and is better than flexibility training. The procedures: The researcher used the experimental method. The subjects were young goalkeepers of the ages 15 – 16 years old who represent the specialized athletic school in Baghdad. They were divided into tow groups. The pilot study was conducted followed by the pretests conducted in 25/6/2008. The two training programs were designed for both groups and were presented to experts in the field. The experiment consisted of two parts; the main part was physical preparation training sessions that took (40) minutes for each group separately starting from 28/6/2008 for (8) weeks training three days per week. Finally the posttests were conducted in 20/8/2008.The researcher used SPSS to treat the results. Conclusions: The researcher concluded the following: 1. Both of the experimental groups showed significant differences and development in the results of the pre and posttests results in favor of the posttests and for both groups in all tests understudy. This showed the affectivity of the training programs on the speed of motor response development. 2. There are significant differences in the posttests' results in favor of the first group that used muscular strength training program in power defined by speed, explosive power and the speed of motor response development tests. 3. There are significant differences in the posttests results in favor of the second group that used flexibility training program in trunk flexion and shoulders flexibility. 4. There are no significant differences between the posttests results of the two groups in arm extension and flexion for 10 seconds. Recommendations: Finally the researcher recommended the following: 1. The necessity of relaying on muscular strength and flexibility training due to their great effect on the development of motor response speed in football goalkeepers. 2. Using modern and standards programs that suit the demands of young goalkeepers. Making similar studies on other physical abilities on other ages of football